Understanding leprosy in a nonendemic area: a pilot study on knowledge, attitudes, beliefs of medical professionals from North-Western Italy - Riccò, Matteo; Vezzosi, Luigi; Ranzieri, Silvia; Balzarini, Federica; Mezzoiuso, Angelo Giosuè; Vaccaro, Fabrizio Giovanni (Acta Biomedica Atenei Parmensis, 2020)
Background. Describing knowledge, attitudes and beliefs about leprosy amongst Medical Professionals in a nonendemic area (Parma Province, North-Western Italy). Methods. A cross-sectional study was carried among a sample of Medical Professionals (MP; No. 242) during June and July 2019 as an on-line self-administered questionnaire including 21 true/false items about epidemiology, diagnosis, and clinical characteristics of leprosy. Effectors of better knowledge status (KS) and higher risk perception (RP) were assessed through calculation of respective multivariate odds ratios (OR) and 95% confidence intervals (95%CI) in two logistic regression analysis models. Results. A total of 102 questionnaires were retrieved (participation rate 42.1%; 67.6% of respondents < 50 year-old). Of them, 10.8% had previously interacted with at least one leprosy case. Knowledge status (KS) was unsatisfying (59.7% correct answers), and also RP was relatively low, as 91.2% of them acknowledged leprosy as a severe disease, but only 42.2% identified leprosy as highly communicable. Knowledge gaps affected particularly understanding of epidemiology and non-dermatological issues. Moreover, 30.4% of respondents ignored that a treated leprosy case may remain in the community before disease eradication. The main effector of KS was having interacted with a leprosy case (OR 4.881 95%CI 1.245-36.905), while RP was negatively associated with a better KS (OR 0.094 95%CI 0.027-0.334), and working as general practitioner (OR 0.133 95%CI 0.031-0.562). Conclusions. While individual expertise of European MP on leprosy slowly disappears, significant knowledge gaps and the high share of misconceptions collectively stress that refresher training may improve early diagnosis and management of incident cases.